Interview control questions - Stylianou, Stelios (My University, 2008)
This study presents a technique for enhancing causal validity in in-depth interview research. The technique is based on the logic of control, as applied in various research contexts such as experiments and statistical analyses. According to this logic, to detect the real effect of an independent variable on a dependent variable, all other variables must be held constant. By using interview control questions (ICQs), this study applies this principle in in-depth interviewing. An ICQ is a probe question that controls an independent variable in the participant's thinking. Two modes are presented: simple control (neutralizing an independent variable to examine whether it is a necessary condition for an outcome) and parallel control (isolating an independent variable to examine whether it is a sufficient condition for an outcome). In both modes, the method allows for additional independent variables to surface. Applications in in-depth interviews exploring attitudes toward victimless deviance are presented. © 2008 Taylor & Francis.
Keywords: Offense; Penalty; Punitive attitudes